Surge in Solar-Powered Homes : Experience in Off-Grid Rural Bangladesh - Khandker, Shahidur R.; Samad, Hussain A.; Sadeque, Zubair K.M.; Asaduzzaman, Mohammed; Yunus, Mohammad; Haque, A.K. Enamul (World Bank, Washington, DC, 2014)
Bangladesh has made remarkable progress in raising living standards and reducing poverty, particularly in previously lagging regions. Rapid solar home system (SHS) expansion in Bangladesh to some 3 million rural households by early 2014 has drawn the attention of donors and governments of other countries. The book s broad aim is twofold: (a) to assess the welfare impact of SHS on households, and (b) to evaluate the present institutional structure and financing mechanisms in place, noting that households want cheaper systems and good quality service while suppliers require a reasonable market-based profit to stay in business. The study entailed an intensive empirical investigation based on both primary and secondary data. The primary data consisted mainly of a large-scale, nationally representative household survey with appropriate geographic spread. Conducted in 2012 by the Bangladesh Institute of Development Studies (BIDS) and assisted by the World Bank, the household survey was designed to examine SHS benefits and costs. The book addresses a number of research issues, which are grouped according to general and gendered household impact, program delivery and monitoring of technical standards, market size and demand, and carbon emissions reduction. The book also analyzes household uses of solar-electric energy services. Typically, SHS models are used for lighting, powering fans and television sets, and charging mobile devices and other electrical equipment. Finally, the book evaluates the gender-disaggregated benefits and women's empowerment from SHS adoption. The gender analysis included two major research questions: (a) can the socioeconomic status of rural women be enhanced by increasing the opportunity to participate in alternative energy-service delivery, and (b) if SHS brings positive impacts in terms of social indicators, what additional efforts can supplement them to bring about a radical shift in gender roles and responsibilities. The book's findings show that better household lighting improves household welfare both directly and indirectly. The book has eight chapters. Chapter one is introduction. Chapter two describes the current status of Bangladesh's SHS expansion program, including salient features of system operation, as well as program delivery and financing. Chapter three reviews the role of electrification in rural development and international experience in using SHS as a complementary solution in remote off-grid areas. Based on the survey data findings, chapter four identifies the major drivers of SHS adoption and system capacity selection at the household and village level, while chapter five discusses and estimates the welfare benefits. Chapter six focuses on SHS market analysis and role of the subsidy, including consumers' willingness to pay and the potential impact of subsidy phase-out. Chapter seven turns to the quality of partner organization (PO) service and other supply-side issues, along with market constraints to meet future demand. Finally, chapter eight offers policy perspectives and a way forward.